2012
DOI: 10.1104/pp.112.194563
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Plasmodesmatal Permeability and Stomatal Patterning by the Glycosyltransferase-Like Protein KOBITO1    

Abstract: The differentiation of stomata provides a convenient model for studying pattern formation in plant tissues. Stomata formation is induced by a set of basic helix-loop-helix transcription factors and inhibited by a signal transduction pathway initiated by TOO MANY MOUTHS (TMM) and ERECTA family (ERf) receptors. The formation of a proper stomata pattern is also dependent upon the restriction of symplastic movement of basic helix-loop-helix transcription factors into neighboring cells, especially in the background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 57 publications
2
29
0
1
Order By: Relevance
“…Our finding that cesa3 je5 mutant seedlings have an approximately 3-fold increase in paired stomata over wild-type controls (Supplemental Fig. S8) supports the hypothesis that perturbation of cellulose production can lead to stomatal cluster formation, an idea proposed in a previous study of the glycosyltransferaselike protein KOBITO1, which is involved in cellulose biosynthesis (Kong et al, 2012). However, exactly how cellulose biosynthesis is involved in regulating stomatal patterning requires further investigation.…”
Section: Discussionsupporting
confidence: 72%
“…Our finding that cesa3 je5 mutant seedlings have an approximately 3-fold increase in paired stomata over wild-type controls (Supplemental Fig. S8) supports the hypothesis that perturbation of cellulose production can lead to stomatal cluster formation, an idea proposed in a previous study of the glycosyltransferaselike protein KOBITO1, which is involved in cellulose biosynthesis (Kong et al, 2012). However, exactly how cellulose biosynthesis is involved in regulating stomatal patterning requires further investigation.…”
Section: Discussionsupporting
confidence: 72%
“…S4). A recent study also identified KOBITO1 as a putative GT and proposed a function in a carbohydrate metabolic process essential for proper plasmodesmata closure (Kong et al, 2012).…”
Section: Identification Of Putative Golgi Gtsmentioning
confidence: 98%
“…2B). One of the potential causes of stomata cluster formation is an increase in plasmodesmata conductivity as in chorus and kobito1-3, two mutants with stomata clustering and multiple other developmental defects (Guseman et al, 2010;Kong et al, 2012). The accumulation of callose at the neck regions of plasmodesmata has a strong impact on conductivity; a decrease in callose deposition leads to plasmodesma opening (Iglesias and Meins, 2000;Levy et al, 2007;Guseman et al, 2010).…”
Section: The Atgpi8 Mutations Affect Many Developmental Processesmentioning
confidence: 99%